Aktivitas Antifungal Minyak Atsiri Cymbopogon nardus L. dan Elettariopsis slahmong Lim. Terhadap Jamur Colletotrichum sp. yang Menyerang Buah Naga Merah (Hylocereus polyrhizus) - Ervina Magdaulih; Nasril Nasir; - Periadnadi (Universitas Andalas, 2014)
Generally the essential oils are antibacterial and antifungal. Cymbopogon nardus which is included in Graminae family commonly produced an essential oil. Another plant Elettariopsis slahmong which is known contains essential oils derived from Zingiberaceae family has not been commonly used. This plant is only used as a spice and salads in Malaysia, Thailand and Indonesia. A study about antifungal activity of essential oil of citronella grass (Cymbopogon nardus L.) and elettariopsis slahmong Lim. against Colletotrichum sp. on Red Dragon Fruit (Hylocereus polyrhizus) was conducted since March to May 2013 in the Laboratory of Microbiology, Department of Biology, Andalas University. This study used experimental method with three dose treatments and three replications for each kind of essential oils. The essential oils were distillated from Cymbopogon nardus and Elettariopsis slahmong. The treatments used 250, 500 and 750 ppm of essential oils. This study found that Cymbopogon nardus could be a potential antifungal prevent Colletotrichum sp. The higher dose was the better preventive effect. There was no effect of Elettariopsis slahmong on Colletotrichum sp.Keywords: essential oil, Cymbopogon nardus, Elettariopsis slahmong, antifungal